Acute Shoshin beriberi syndrome immediately post–kidney transplant with rapid recovery after thiamine administration. (24th May 2019) - Elias, Isaac M.; Sinclair, Graham; Blydt‐Hansen, Tom D.
Abstract: Pediatric kidney transplant surgery is usually well tolerated, despite suboptimal physical conditioning that may result from uremia and nutritional deficiencies that accompany end‐stage kidney failure. Nutritional supplementation is used to overcome such deficiencies, especially for children needing dialysis. Thiamine, a water‐soluble vitamin also known as vitamin B1, is a critical cofactor in energy metabolism and may be competitively inhibited by the antimetabolite oxythiamine, a uremic toxin that accumulates in kidney failure. We report a case of a thiamine deficiency syndrome leading to overwhelming cardiac dysfunction, metabolic instability, and hemodynamic compromise, after otherwise uneventful kidney transplant surgery. Prior to transplant, this 14‐year‐old boy was treated with peritoneal dialysis and received thiamine supplementation. Post‐transplant, the patient first developed hyperglycemia, then lactic acidosis, and subsequently hemodynamic instability despite escalating treatment with volume resuscitation and inotropic medication. He made a rapid and complete recovery after administration of IV thiamine. This is the first reported case of Shoshin beriberi syndrome in a pediatric kidney transplant recipient. Inadequate dialysis may have been a key factor, with toxin accumulation and thiamine transporter downregulation contributing to his status. Functional thiamine deficiency should be considered as a potential treatable cause of early post‐transplant hemodynamic instability.